Housing Segregation, Negro Employment, and Metropolitan Decentralization - Kain, John F. (Quarterly Journal of Economics, 1968)
I. Negro residential segregation, 176. — II. Segregation in Detroit and Chicago, 178. — III. The distribution of negro employment, 179. — IV. Negro employment by occupation and industry, 183. — V. The level of nonwhite employment, 189. — VI. Suburbanization and negro employment, 191. — VII. Postwar dispersal of employment and population in Chicago, 192. — VIII. Conclusions, 196.